Psychological State Among the General Chinese Population Before and During the COVID-19 Epidemic: A Network Analysis - Ge, Fenfen; Zheng, Anni; Wan, Mengtong; Luo, Guan; Zhang, Jun (Frontiers in Psychiatry, 2021)
Background: The infectious disease Coronavirus Disease 2019 (COVID-19) outbreak in 2019 spread to multiple countries. The quick spread of the virus and isolation strategies may trigger psychological problems. Our aim was to explore the dynamic network structure of the psychological state before and during the epidemic. Methods: A web-based survey was conducted in two stages: the T1 stage (January 1, 2019 to December 31, 2019) and the T2 stage (February 1, 2020 to March 8, 2020). In both stages, the Patient Health Questionnaire-9, General Anxiety Disorder-7, and Pittsburgh Sleep Quality Index were used to assess depression, anxiety and sleep, respectively. Results: We matched the data based on IP addresses. We included 1978, 1547 and 2061 individuals who completed the depression, anxiety, and sleep assessments, respectively, at both stages. During epidemics, psychomotor agitation/retardation, inability to relax, restless behavior and the frequency of using medicine had high centrality. Meanwhile, the network structure of psychological symptoms becomes stronger than before the epidemic. Conclusion: Symptoms of psychomotor agitation/retardation, inability to relax and restless behavior should be treated preferentially. It is necessary to provide mental health services, including timely and effective early psychological intervention. In addition, we should also pay attention to the way patients use medicines to promote sleep quality.